A new meroterpenoid and a new polyketide from Penicillium expansum GY618 Fungus. (October 2022) - Zhu, Qianheng; Zang, Yi; Luo, Juanjuan; Hou, Wen; Lei, Liang; Huang, Jiuzhong; Luo, Nianhua; Gao, Yanping; Ouyang, Sheng; Huang, Hao; Wen, Huiling
Abstract: Two new compounds, including one meroterpenoid (1 ) and a polyketide derivative (2 ), along with six compounds (3 −8 ), were isolated from the rice solid fermentation of Penicillium expansum GY618. The structures of these new compounds were elucidated through interpretations of spectroscopic data and highresolution electrospray ionization mass spectrometry. The absolute configurations of all new compounds were unambiguously established through the optical rotation or calculation of the ECD spectrum. All isolated compounds were evaluated for their antibacterial and antitumor activities. Compound 6 exhibited weak antitumor activity. Graphical Abstract: ga1 Highlights: One new meroterpenoid and a new polyketide derivative were isolated. The absolute configuration of all new compounds was unambiguously established. Compound 6 showed weak antitumor activity.